Biofilm lifestyle enhances diesel bioremediation and biosurfactant production in the Antarctic polyhydroxyalkanoate producer Pseudomonas extremaustralis - Tribelli, Paula Maria; Di Martino, Carla; López, Nancy Irene; Raiger Iustman, Laura Judith (Biodegradation)
Diesel is a widely distributed pollutant. Bioremediation of this kind of compounds requires the use of microorganisms able to survive and adapt to contaminated environments. Pseudomonas extremaustralis is an Antarctic bacterium with a remarkable survival capability associated to polyhydroxyalkanoates (PHAs) production. This strain was used to investigate the effect of cell growth conditions-in biofilm versus shaken flask cultures-as well as the inocula characteristics associated with PHAs accumulation, on diesel degradation. Biofilms showed increased cell growth, biosurfactant production and diesel degradation compared with that obtained in shaken flask cultures. PHA accumulation decreased biofilm cell attachment and enhanced biosurfactant production. Degradation of long-chain and branched alkanes was observed in biofilms, while in shaken flasks only medium-chain length alkanes were degraded. This work shows that the PHA accumulating bacterium P. extremaustralis can be a good candidate to be used as hydrocarbon bioremediation agent, especially in extreme environments. © 2012 Springer Science+Business Media B.V. Fil: Tribelli, Paula Maria. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales; Argentina Fil: Di Martino, Carla. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales; Argentina Fil: López, Nancy Irene. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad ...